2020
DOI: 10.1186/s13054-020-02923-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist versus pressure support ventilation: a randomized controlled feasibility trial performed in patients at risk of prolonged mechanical ventilation

Abstract: Background: The clinical effectiveness of neurally adjusted ventilatory assist (NAVA) has yet to be demonstrated, and preliminary studies are required. The study aim was to assess the feasibility of a randomized controlled trial (RCT) of NAVA versus pressure support ventilation (PSV) in critically ill adults at risk of prolonged mechanical ventilation (MV). Methods: An open-label, parallel, feasibility RCT (n = 78) in four ICUs of one university-affiliated hospital. The primary outcome was mode adherence (perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Since all that is set during NAVA is the proportion of effort provided by the ventilator to supplement the patient's ventilatory drive, for a given NAVA level, the airway pressure varies breath-by-breath in proportion to Edi. Three randomized controlled trials on NAVA have been previously published [9,11,12]. Demoule et al [9] randomized 128 patients ready for partial ventilatory support to NAVA or pressure support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since all that is set during NAVA is the proportion of effort provided by the ventilator to supplement the patient's ventilatory drive, for a given NAVA level, the airway pressure varies breath-by-breath in proportion to Edi. Three randomized controlled trials on NAVA have been previously published [9,11,12]. Demoule et al [9] randomized 128 patients ready for partial ventilatory support to NAVA or pressure support.…”
Section: Discussionmentioning
confidence: 99%
“…NAVA did not affect mortality. Hadfield et al [11] randomized 78 patients at risk for prolonged MV to receive NAVA or pressure support. They found that NAVA was associated with more VFDs, however, no significant differences were observed in duration of MV, ICU or hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, NAVA reduced patient-ventilator asynchrony and the rate of post-extubation application of non-invasive ventilation, and feasibility and safety of NAVA over several days was successfully demonstrated. A recent study confirmed acceptable adherence to the assigned mode beyond 48 h when comparing NAVA with PSV [ 21 ]. Furthermore, Liu et al recently showed shorter weaning duration with NAVA compared to PSV in selected difficult-to-wean patients [ 20 ].…”
Section: Differences Between Proportional Modes and Psvmentioning
confidence: 85%
“…Moreover, safe targets for respiratory effort may vary among patients, depending on the severity of lung injury and diaphragm function [ 15 17 ]. The uncertainty regarding titration of inspiratory support with NAVA and PAV+ might be one of the reasons why there is still limited data showing improved clinical outcomes when using proportional modes as compared to conventional modes [ 18 , 19 ], but clinical benefits of NAVA compared to PSV were recently demonstrated in difficult-to-wean patients [ 20 , 21 ]. At the same time, despite having very complex physiological consequences, PSV maintains an appearance of simplicity and is the most frequently used partially supported mode of ventilation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%